2016
DOI: 10.1007/s10661-016-5456-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the causality of changes in the landscape pattern of Lake Urmia basin, Iran using remote sensing and time series analysis

Abstract: Lake Urmia is the second largest hypersaline lake in the world in terms of surface area. In recent decades, the drop in water level of the lake has been one of the most important environmental issues in Iran. At present, the entire basin is threatened due to abrupt decline of the lake's water level and the consequent increase in salinity. Despite the numerous studies, there is still an ambiguity about the main cause of this environmental crisis. This paper is an attempt to detect the changes in the landscape s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The LU basin's semi-arid climate shows considerable seasonal variations in air temperature, generally between 0 and -20°C in winter and up to 40°C in summer (Mehrian et al 2016). Annual precipitation varies between 300 and 400 mm, 77% of which occurs between December and May, while the annual evaporation rate from the lake surface is approximately 1000 mm.…”
Section: Research Areamentioning
confidence: 99%
See 2 more Smart Citations
“…The LU basin's semi-arid climate shows considerable seasonal variations in air temperature, generally between 0 and -20°C in winter and up to 40°C in summer (Mehrian et al 2016). Annual precipitation varies between 300 and 400 mm, 77% of which occurs between December and May, while the annual evaporation rate from the lake surface is approximately 1000 mm.…”
Section: Research Areamentioning
confidence: 99%
“…The causes of the enormous water loss of Lake Urmia are manifold and continue to be extensively studied and discussed in the scientific community (Hassanzadeh et al 2012;Mehrian et al 2016;Shadkam et al 2016;Talebi et al 2016;Khazaei et al 2019). Generally, the decline is blamed on a combination of climate change and human-induced drivers (Agha Kouchak et al 2014;Jalili et al 2016;Alizadeh-Choobari et al 2016;Ghale et al 2017;Arkian et al 2018;Chaudhari et al 2018).…”
Section: Causes Of Lake Urmia's Desiccationmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies also confirmed that drought leads to airborne salt-dust scatter 7 , 14 , 31 33 . When the saline flow sources around the lake are activated during monsoon season, they emit a wave of salt-dust into the air that can reach the neighboring cities 34 . The atmospheric aerosol is a complex and dynamic combination of solid and liquid particles affected by natural phenomena and human activities 35 .…”
Section: Study Areamentioning
confidence: 99%
“…Furthermore, the water level of Lake Urmia has decreased from 1270.64 to 1270.38 cm in 2011, showing a 0.26 cm decline in 1 year. Some researchers believe that the dam construction on the upstream rivers is the main contributing factor in declining of the Urmia Lake water level [53,54]. At the same time, the water authorities claim that climate change is the main reason [24,55].…”
Section: Causes Of the Lake Shrinkingmentioning
confidence: 99%